The Influence of Knowledge Management and Learning Organizations on High School Employee Performance in Tangerang - Denok Sunarsi; Umi Rusilowati; Suwanto Suwanto; Azhar Affandi; Haedar Akib (Journal of Educational Science and Technology (EST), 2021)
This study aims to determine whether knowledge management and learning organization has an effect on employee performance at high school in Tangerang. Research data collected from questionnaires filled out by 180 respondents and the method used is the method quantitative research using structural equation modeling (SEM) analysis with the statistical tool SmartPLS 3.0. The results showed that knowledge management has a positive and significant effect on employee performance. In addition, learning organization has a positive and significant effect on employee performance. This research recommends companies to continue to pay attention to the application of knowledge management and learning organizations so that can run effectively to improve the performance of high school employees in Tangerang.